2022
DOI: 10.1093/femsyr/foac045
|View full text |Cite
|
Sign up to set email alerts
|

Erg6p is essential for antifungal drug resistance, plasma membrane properties and cell wall integrity in Candida glabrata

Abstract: ERG6 gene encodes C-24 methyltransferase, one of the specific enzymes that differ in mammalian and yeast sterol biosynthesis. To explore the function of CgErg6p in the yeast pathogen Candida glabrata, we have constructed the Cgerg6Δ deletion mutant. We found that C. glabrata cells lacking CgErg6p exhibit reduced susceptibility to both antifungal azoles and polyenes. The reduced content of ergosterol in the Cgerg6 deletion mutant was accompanied by increased expression of genes encoding the last steps of the er… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…In two recent studies, ERG6 was found to be essential in iron homeostasis, oxidative and membrane stress tolerance in C. glabrata 68,69 , which might explain the lower SR for H2O2, SDS and EDTA of the sterol alteration type 4 strains observed (Figure 4). Interestingly, a general increased (relative to wt) resistance to cell wall stressors (CFW and CR) accompanies the LoF of ERG6 (Fugure 4), which suggests a role of ERG6 in cell wall integrity as shown in C. glabrata 69 . A recent study shows that three AMB resistant clinical isolates show hyper resistance towards cell wall perturbating agents such as CFW, CR and caffeine, compared to an AMB susceptible strain 24 .…”
Section: Discussionmentioning
confidence: 85%
“…In two recent studies, ERG6 was found to be essential in iron homeostasis, oxidative and membrane stress tolerance in C. glabrata 68,69 , which might explain the lower SR for H2O2, SDS and EDTA of the sterol alteration type 4 strains observed (Figure 4). Interestingly, a general increased (relative to wt) resistance to cell wall stressors (CFW and CR) accompanies the LoF of ERG6 (Fugure 4), which suggests a role of ERG6 in cell wall integrity as shown in C. glabrata 69 . A recent study shows that three AMB resistant clinical isolates show hyper resistance towards cell wall perturbating agents such as CFW, CR and caffeine, compared to an AMB susceptible strain 24 .…”
Section: Discussionmentioning
confidence: 85%
“…Increased susceptibility has been reported for erg6 null mutants of S. cerevisiae , K. lactis and C. neoformans 14 , 17 , whereas a C. albicans Δerg6 mutant maintains wild-type susceptibility profiles 16 . C. glabrata and C. auris clinical isolates with erg6 mutation displays increased susceptibility to triazoles 37 , 50 , but C. glabrata null mutants generated in laboratory strains revealed increased tolerance 15 . Additionally, reduced resistance to triazoles has been reported in several erg null mutants along with ergosterol reduction or depletion 53 55 .…”
Section: Discussionmentioning
confidence: 99%
“…Notably, in our study we found that Erg6A is essential for the viability of A. fumigatus. In contrast, Erg6A homologes of yeasts are not essential for viability 22,30,31 . Consequently, the sterol C24-methyltransferase could represent a specific antifungal target in fungi that have an ergosterol biosynthesis pathway similar to that of A. fumigatus, similar as it was proposed recently 32 .…”
Section: Discussionmentioning
confidence: 96%